The Effect Digitalization Zakat Payment Against Potential of Zakat Acceptance in National Amil Zakat Agency - Pertiwi Utami; Tulus Suryanto; M. Nasor; Ruslan Abdul Ghofur (IQTISHADIA, 2020)
The purpose of this study was to determine the effect of digitalization zakat payments on the potential for zakat acceptance at the BAZNAS Jakarta center. The originality of this research lies in the digitalization analysis of zakat payments to increase the potential for receiving BAZNAS center based on sharia economic approaches, and digital technology theory. The research method used is associative quantitative using a simple linear regression analysis technique with a sample size of 170 respondents selected based on purposive sampling technique. From the results of data analysis using SPSS 19.0, an R-value of 74.8% was obtained, which means that the relationship between the digitalization of zakat payments and the potential for receiving zakat at the BAZNAS is strong.  The findings show that the digitalization variable of zakat payment or zakat payment (X) influences the potential for zakat receipt (Y) of 55.9%, and the remaining 40.1% is influenced by other factors not considered. Based on the results of deepening between the theory and practice of digital zakat revealed that the challenges in efforts to increase the potential for digital zakat acceptance in Indonesia are internet access which is still weak and uneven in Indonesian territory, building an 'attachment' relationship between mustahiq, muzzaki and BAZNAS, and the application of principles of sharia in the management of zakat. Therefore, the research explains the strategies that can be done to answer the challenges of digital zakat.